Unraveling GLUT‐mediated transcytosis pathway of glycosylated nanodisks - Huan Wang; Zui Zhang; Juan Guan; Weiyue Lu; Changyou Zhan (Elsevier, 2021)
Glucose transporter (GLUT)-mediated transcytosis has been validated as an efficient method to cross the blood-brain barrier and enhance brain transport of nanomedicines. However, the transcytosis process remains elusive. Glycopeptide-modified nanodisks (Gly-A7R-NDs), which demonstrated high capacity of brain targeting via GLUT-mediated transcytosis in our previous reports, were utilized to better understand the whole transcytosis process. Gly-A7R-NDs internalized brain capillary endothelial cells mainly via GLUT-mediated/clathrin dependent endocytosis and macropinocytosis. The intracellular Gly-A7R-NDs remained intact, and the main excretion route of Gly-A7R-NDs was lysosomal exocytosis. Glycosylation of nanomedicine was crucial in GLUT-mediated transcytosis, while morphology did not affect the efficiency. This study highlights the pivotal roles of lysosomal exocytosis in the process of GLUT-mediated transcytosis, providing a new impetus to development of brain targeting drug delivery by accelerating lysosomal exocytosis.